Introduction: "Love Jihad": Sexuality, Reproduction and the Construction of the Predatory Muslim Male - Frydenlund, Iselin (Religions, 2022)
The Introduction to this Special Issue on ‘"Love Jihad": Sexuality, Reproduction and the Construction of the Predatory Muslim Male’ provides a theoretical overview and suggests an analytical lens for how to understand "Love Jihad" and related notions of Islamization through marriage, sexuality, and reproduction. We define "Love Jihad" as the notion that Muslim men intentionally and strategically allure and entrap non-Muslim women with the intent to marry and convert them to Islam as part of an Islamization project. We suggest a two-fold understanding of the concept of "Love Jihad". First, the concept needs to be understood as a globalizing trope, originating from India and spreading to a wide range of cultural and national contexts across the world. Second, we propose to understand the specific term "love jihad" beyond its referential specificity, and thereby broadening it into an analytical concept for exploring related concepts (such as "sexual jihad" and "demographic jihad"), as well as related notions of Muslim men as sexual predators (in certain geographical settings known as "rapefugees"). We therefore include in our analysis related notions such as Islamic womb fare, "grooming", "The Great Replacement", and "unethical conversion" in marriage where they relate to flows of gendered nationalist imaginaries of the Muslim "Other". The aim of this Introduction—as well as the Special Issue—is to contribute to the study of Islamophobia as a global phenomenon and to deepen our understanding of the gendered imaginaries of anti-Muslim nationalist formations across the world.